Research Paper Writing: The Task Dependency Principle as a Tool in Developing Learner Independence - Šeškauskienė, Inesa (Kalbotyra, 2006)
The present paper sets out to examine the efficiency of the Task Dependency Principle (TDP) in teaching research paper writing for BA students in English Philology. So far the TDP has been used in teaching practical language skills to non-native speakers. It consists in giving students tasks which are based on previously accomplished tasks. The TDP has turned out to be very effective in teaching research paper writing skills as well. Implemented throughout one full semester of the research-in-progress seminar, coupled with the peer review and fostered by the focus on individually selected linguistic topics, the TDP has contributed to increasing the motivation of students and shifting from teacherto student-centred teaching/learning.